Riyadhah: The model of the character education based on sufistic counseling - Bassar, Agus Samsul; Hasanah, Aan (Journal of Advanced Guidance and Counseling, 2020)
The purpose of education did not only build intelligent people, but also built a strong character and noble character based on the noble values of the nation and religion. Then, a quality and holistic character education becomes a necessity for the Indonesian people who want to develop the potential of the nations to have spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state. Character education in Islam is a moral education which is the essence of Islamic teachings. For example, the character education applied by the Sufis with various riyadhah in their zawiyah or ribath under the guidance of the murshid who becomes a role model in the process of habituating and disciplining students. This study aimed to explore the model of the character education based on sufistic counseling with the various riyadhah in guiding students to have noble character. This descriptive study used a qualitative approach by a literature study and case study in the field. The research found that the process of character internalization carried out through various riyadhah is a spiritual practice covering all aspects of life, both worship and muamalah in an effort to maintain a harmonious relationship between humans and Allah, humans with other humans, humans with their environment, and humans with themselves. Therefore, it is be able to clean the spirit and to devote themselves to the Divine, by having character or noble character and always doing good in life.